Public Transport System in Local City and Rural Area: Comparative Study Between Malaysia and Japan - Sotaro Yukawa; Mohd Azizul Ladin; Amiruddin Ismail; Riza Atiq Abdullah O.K. Rahmat (UTM, 2014)
Recently, bus companies in Peninsular Malaysia are confronted with a crisis of maintaining its local bus services. Operating unprofitable public transport system in local cities and rural areas is an important issue in a developed country. However, such cases (operating unprofitable public transport) have emerged in developing country like Malaysia. Until recently, researchers focused on this kind of problems for only developed country and there are not enough international comparison about local bus service. To address this gap, we conducted a comparative analysis between Japan and Malaysia in this paper. We’ll focus on the similarities and differences in terms of regulation, policy and some cases of bus substitution in both countries. We also examined the advantages and disadvantages about Japanese case and present some implication about future policy in Malaysia